Development of Variable Side Mold for Free-Form Concrete Panel Production - Jongyoung Youn; Jiyeong Yun; Jihye Kim; Donghoon Lee (Buildings, 2022)
With the increase of free-form architecture, many studies have been conducted for producing free-form Concrete Panels (FCP), but there are still areas that are lacking in terms of the technological aspect. In particular, as free-form panels are produced by hand, the precision of the shapes is low and cost and time are high. FCP production equipment was developed to resolve this. In this study, the variable side mold for FCP production used in side control equipment among FCP production equipment was developed. Variable side mold is equipment that satisfies five requirements to configure the form of FCPs. The variable side mold is made with steel plates so that it can withstand the side pressure of concrete. As a result, the material has a uniform thickness throughout and is molded to the desired shape. Therefore, in order to verify this, the panel was manufactured as a variable side mold to compare the side form with the designed form through 3D scanning and quality inspection to check for errors. As a result, there was a 0.276 mm mean difference for both ends of the panel and the central part, and it was therefore verified through t-test that errors occurred within the allowed margin of 95% confidence level.